Atrial Premature Depolarization‐Induced Changes in QRS and T Wave Morphology on Resting Electrocardiograms in Horses. (21st May 2016) - Broux, B.; De Clercq, D.; Decloedt, A.; Van Der Vekens, N.; Verheyen, T.; Ven, S.; Pardon, B.; van Loon, G.
Abstract : Background: The electrocardiographic differentiation between atrial (APDs) and ventricular (VPDs) premature depolarizations is important. P wave prematurity and normal QRS and T wave morphology generally are used as discriminating criteria for APDs. Hypothesis/Objectives: The aim of this study was to determine whether P, Q, R, S, and T wave amplitude, PQ interval, QRS and P wave duration and P and T wave morphology differ between APDs and sinus beats. To determine the relationship between the RR coupling interval and the change in S wave amplitude between sinus beats and APDs. Methods: Case–control study. From a modified base‐apex configuration of 30 horses with APDs at rest, sinus beat and APD associated preceding RR interval, P, PQ and QRS duration and P, R, S, and T wave amplitudes were measured. Linear mixed models and logistic regression were used to determine the effect of APDs on the ECG variables studied. Results: In comparison to sinus beats, APDs were associated with a significant ( P < .001) change in P amplitude (−0.03 ± 0.01 mV) and increase in S (0.20 ± 0.02 mV) and T (0.08 ± 0.03 mV) amplitude. PQ (−20.3 ± 5.2 ms) and RR (−519 ± 14 ms) interval and P duration (−21.1 ± 3.0 ms) decreased ( P < .001). APDs were significantly associated with a singular positive P wave (OR: 11.0, P < .001) and were more likely to have a monophasic positive T wave (OR: 9.2, P < .001). A smaller RR coupling interval was associated with an increased relative difference in S amplitude ( P < .01). Conclusions: Atrial premature depolarizations may lead to changes in QRS and T wave morphology. Knowledge of these changes is important to avoid interpreting certain APDs as VPDs.